Coordination and Driving Mechanism of Water-Energy-Food-Ecology Coupling System in Inner-Mongolia Reaches of Yellow River Based on Coupling Coordination Degree Model - TAN Hanze; ZHANG Zezhong; FENG Kai; LUO Xudong; ZHOU Quancheng; LIU Yong; ZHANG Dequan (Renmin Zhujiang)
In order to realize the high quality and sustainable development of the Inner-Mongolia Reaches of Yellow River, this paper took Dalad Banner and its townships as research objects and constructed a water-energy-food-ecology (W-E-F-E) coupling coordination evaluation index system. The coupling coordination degree model was used to carry out system coordination research based on the W-E-F-E system coupling from the temporal and spatial perspectives, and the gray correlation model and the geographic detector were used to explore the driving mechanisms. The results show that: ① The comprehensive evaluation index of the W-E-F-E system in the Dalad Banner region generally shows a slow upward trend, from 0.356 in 2000 to 0.575 in 2022. ② The coupling degree of the W-E-F-E system in Dalad Banner and its townships is high, and it is in the stage of high-level coupling (The mean value is 0.967). However, the coupling coordination degree is low and maintains at the primary coordination stage (The mean value is 0.668). Unbalanced and uncoordinated spatial development exists in the Dalad Banner region, mainly in the eastern part of Dalad Banner, and areas with a higher coordination degree gradually change from the west to the center. ③ The coordination of the W-E-F-E system of Dalad Banner and its townships shows a good trend on the whole, and the whole region is gradually developing into a good coordination stage. The townships have basically entered the intermediate coordination stage. ④ In general, the influence degree of driving factors on the system coupling coordination degree is as follows: ecology > water > energy > food. In terms of spatial differences, energy has the greatest impact, while water has the least explanatory power. The interaction among water, food, and ecology yields the greatest explanatory power. The results can provide a basis for decision-making on the efficient utilization of resources and habitat protection in the Inner-Mongolia Reaches of Yellow River.